Milk-clotting enzymes: S.elaeagnifolium as an alternative source - Lopez Diaz, Jose Alberto (Apple Academic Press, 2020)
Proteases are one of the most used enzymes in the food industry, including the dairy industry. The coagulation of milk requires a protease capable of hydrolyzing caseins in such a way that electrostatic and steric repulsion be reduced. Animal-origin proteases like chymosin and pepsin have been used for centuries as milk coagulants. Nowadays, microbial proteases and recombinant calf rennet are commercially available. However, different factors such as religious or ethical concerns, diet, and price, have promoted the search for alternative milk coagulants. In this book chapter, it will be addressed and discussed the most recent information about milk-clotting proteases from the fruits of S. elaeagnifolium, an endemic plant from the northeast of Mexico, the southwest of the United States, and Argentina.